Fungsi Change Management dalam Implementasi ERP untuk Mendukung Otomatisasi Proses Bisnis: Systematic Literature Review - Nadya Salsabillah Chriswanda; Ade Sobandi; Fahmi Jahidah Islamy (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The implementation of Enterprise Resource Planning (ERP) is a complex organizational transformation process and requires effective change management to minimize the risk of failure. Although the relationship between change management and ERP implementation has been widely discussed, studies that integrate the two in the context of business process automation are still limited. This study aims to analyze the role of change management in ERP implementation and its contribution to business process automation through the Systematic Literature Review (SLR) method with the PRISMA protocol on 19 articles obtained from Scopus and Google Scholar for the 2019–2026 period. The results show that change management plays an important role in increasing organizational readiness, supporting ERP adoption, and strengthening the success of business process automation. ERP implementation allows for cross-functional process integration, workflow standardization, and increased operational efficiency through the use of digital technology. This research proposes an integrative conceptual framework that connects change management, ERP implementation, and business process automation as a digital transformation strategy that supports the improvement of organizational performance and competitiveness.